Some Evaluation Aspects of Atmospheric Aerosol in Industrial Centers on The Basis Ofsatellite Information - Azizov, B.M.; Khalilova, Kh.S. (Herald of Azerbaijan Engineering Academy, 2021)
The main purpose of the study of atmospheric aerosols is to determine their impact on the Earth's radiation balance and climate change on a regional and global scale. Because aerosols vary in size, shape, composition, and duration in the atmosphere, they are evaluated in the terrestrial atmosphere and at different altitudes via satellite systems. In the article under review, the study of atmospheric aerosols in large industrial centers was carried out on the basis of mutual analysis of surface and satellite data. It has been shown that the correct estimation of aerosol attenuation of the signal depends directly on the choice of spectral wavelength (0.4 μm to 11.3 μm). Surface measurement results, data from Landsat-7.8 and AZERSKY satellites were used in the research. The article focuses on the assessment of NO2, SO2 and large dispersed aerosols, which are typical for industrial centers.